Fusion peptide constructs from antigens of M. tuberculosis producing high T-cell mediated immune response. - Shaista Arif; Mohsina Akhter; Aasia Khaliq; Muhammad Waheed Akhtar (PLoS ONE, 2022)
Non availability of effective anti-TB vaccine impedes TB control which remains a crucial global health issue. A fusion molecule based on immunogenic antigens specific to different growth phases of Mycobacterium tuberculosis can enhance T-cell responses required for developing a potent vaccine. In this study, six antigens including EspC, TB10.4, HspX, PPE57, CFP21 and Rv1352 were selected for constructing EspC-TB10.4 (bifu25), TnCFP21-Rv1352 (bifu29), HspX-EspC-TB10.4 (trifu37), HspX-TnCFP21-Rv1352 (trifu44) and HspX-EspC-TB10.4-PPE57 (tetrafu56) fusion proteins. Th1-cell epitopes of EspC, PPE57 and Rv1352 antigens were predicted for the first time using different in silico tools. The fusion molecule tetrafu56, which consisted of antigens from both the replicating and the dormant stages of Mtb, induced a release of 397 pg/mL of IFN-γ from PBMCs of the active TB patients. This response was comparable to the response obtained with cocktail of the component antigens (396 pg/mL) as well as to the total of the responses obtained separately for each of its component antigens (388 pg/mL). However, PBMCs from healthy samples in response to tetrafu56 showed IFN-γ release of only 26.0 pg/mL Thus a previous exposure of PBMCs to Mtb antigens in TB plasma samples resulted in 15-fold increase in IFN-γ response to tetrafu56 as compared to the PBMCs from the healthy controls. Hence, most of the T-cell epitopes of the individual antigens seem to be available for T-cell interactions in the form of the fusion. Further investigation in animal models should substantiate the immune efficacy of the fusion molecule. Thus, the fusion tetrafu56 seems to be a potential candidate for developing an effective multistage vaccine against TB.